Different responses to glucose overload between two strains of largemouth bass (Micropterus salmoides) - Lei, Caixia; Xie, Yujing; Song, Hongmei; Jiang, Peng; Du, Jinxing; Li, Shengjie (Frontiers in Physiology, 2022)
In order to improve the glucose utilization capacity of largemouth bass (Micropterus salmoides), differences in glucose homeostasis regulation between two strains (Y: breeding strain; W: wild strain) were compared after glucose injection. The data revealed that plasma glucose in the Y strain (<12 h) recovered faster than in the W strain (12 h), with the Y strain secreting more insulin within 6 hours post-injection. Triglyceride (TG) and low- density lipoprotein-cholesterol (VLDL-CH) content in the Y strain increased, peaking at 12 h, then decreased, whereas the W strain’s TG content was not affected and VLDL-CH content decreased. The hepatic and muscular fatty acid synthetase, liver x receptor-1, and sterol regulatory element-binding protein expressions were consistent with the TG content change. Both strains’ liver and muscle glycogen contents exhibited similar trends to that of the glycogen synthase gene—increasing, then declining, and peaking at 6 and 12 h. The expression levels of hepatic and muscular phosphofructokinase and pyruvate kinase in the Y strain increased, peaking at 12 h. In the W strain, they were suppressed and reached the minimum at 24 h. The mRNA levels of hepatic and muscular phosphoenolpyruvate carboxykinase and glucose-6-phosphatase were enhanced and peaked at 24 h in both strains, hepatic isocitrate dehydrogenase-1 and α-ketoglutarate dehydrogenase complex expression increased after declining, peaking at 12 and 24 h. Two genes in the W strain’s muscles showed a similar trend. Both strains’ transcriptome results identified seven common functional genes for resistance to hyperglycemia that were involved in the circadian rhythm pathway, which is a suggested key pathway for coping with hyperglycemia. Furthermore, 48 differential genes were identified between the two strains, and these genes were enriched in the TGF-beta and cell cycle signaling pathways, indicating that these pathways may be key factors affecting the differential regulation of glucose homeostasis. We conducted a comprehensive comparison of glucose homeostasis molecular regulation between two strains of M. salmoides, and the results can provide a promising strategy to improve the glucose utilization capacity of M. salmoides based on advantageous pre-existing traits.